Observasi Partisipatif dalam Pencegahan Demam Berdarah Dengue di Desa Gili Anyar Bangkalan - Widitya Qomaro, Galuh; Nasrulloh, Nasrulloh; Havida, Lailatul Wahyu; Dewi Anggraeni, Dyah Ayu Ratna (Keris: Journal of Community Engagement, 2024)
The Dengue Hemorrhagic Fever (DHF) is still one of the main health problems of Indonesian society. Usually, this disease which originates from the Aedes aegypti and Aedes albopictus mosquitoes often occurs during the rainy season. The number of dengue fever cases in Bangkalan for the period 1-20 January 2023 was recorded at 27 cases with 1 death. Community concern for the surrounding environment is one of the factors in increasing healthy living behavior. There is a need to increase public awareness of the environmental conditions of slum settlements in preventing Dengue Hemorrhagic Fever in residential environments. In general, the implementation of community service uses the participatory observation method. The participatory observation method has several stages, including: 1) Initial observation. 2) Participation. 3) Observation. 4) Reflection. 5) Analysis and interpretation. Community service related to preventing dengue fever outbreaks is carried out through providing education regarding environmental cleanliness and health to mothers in the Gili Anyar Kamal Bangkalan Village area through 3 (three) stages, namely: 1) pre-test to determine the audience's level of understanding regarding environmental health and dengue fever; 2) education about health and environmental health, prevention methods and community participation in handling dengue fever; 3) post-test to measure the mother's knowledge after carrying out community service activities. The results of the outreach were proven to increase public understanding regarding Dengue Hemorrhagic Fever with an increase in scores of 35.8%. In order to combat dengue fever, community participation is very important. By taking steps to prevent the spread of dengue fever, communities can help fight this disease and protect their personal health and that of their surrounding communities